Answer :

Given:


Now, am = a + (m – 1)d



an + n(m – 1)d = 1


an + mnd – nd = 1 …(i)




am + mnd – md = 1 …(ii)


From eq. (i) and (ii), we get


an + mnd – nd = am + mnd – md


an – am – nd + md = 0


a(n – m) – d (n – m) = 0


a = d


Now, putting the value of a in eq. (i), we get


dn + mnd – nd = 1


mnd = 1



Hence,


Now, (mn)th terms of AP is


amn = a + (mn – 1)d




amn = 1


Hence Proved


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses